Formal generation in structure Decorative gadflies (Journal of the College of Basic Education, 2023)
It is well known that Arab Islamic art is a decorative art, developed by Muslim artistsWhere they turned away from drawing living beings for their hatred, especially in the early eras of Islam; ResultingThis leads to the use of various other decorations (geometric - botanical - linear text); embodied by decoratingThe Holy Quran and Islamic architecture; Over time, these decorations evolved; So I got pregnant in structureIts units and formal elements are a feature described by its Islamic decorative character.where wolves starve as a complement to calligraphic decorative work; As it formed its groupThe integrated personality is an ornamental field, no matter how much it helped to beautify many applications on the levelLinear achievements that were artistically inspired and designed to meet aesthetic and taste goals.This is based on the diversity and contrast arising in its design structure of vocabulary and elementsapproved and even within the same direction, as well as the existence of different formal Tdladat representedIt has decorative flywheels, which are as follows:1 Decorative botanical cotyledons (twig-sepals-flowering).7" Geometric Flies.3 double decorative cotyledons (vegetal-geometric).These formal reproductions were adopted in many applications, especially the linear paintings that are consideredThis is our field of research.Where the researcher found that one of the difficulties he faces in this field is the great diversityfor implemented designs. In addition to their abundance, we will not exaggerate if we say that there are no models that can beRest assured that this is an adequate example of this diversity of decorative gadflies; meaning to be embodied in itAll the design possibilities are actually implemented, and in light of that, the researcher tried to focus his efforts on